Collaborative Nonverbal Interaction within Virtual Environments - Adriana Peña Pérez Negrón (ReCIBE)
Current virtual environments are predominantly visual-spatial, which allows their ‘inhabitants’ the display, either in a conscious or unconscious way, of nonverbal cues during interaction, such as gaze direction, deictic gestures or location. This interchange of nonverbal messages enriches interaction while supports mutual comprehension, fundamental for collaborative work and therefore particularly important in a multiuser virtual environment, that is, a Collaborative Virtual Environment. Different techniques, the media involvement, and automatic detection related collaborative nonverbal interaction are here discussed.